Liquid tin interactions with ISTTOK plasmas - Loureiro, J.P.S.; Iafrati, M.; Fernandes, H.; Mazzitelli, G.; Silva, C.; Gomes, R.; Pereira, T.; Figueiredo, H.; Alves, H. (Fusion engineering and design, 2019)
Materials such as lithium, gallium and tin have been proposed as candidates for liquid metals plasma facing components. The properties of these materials introduce novel methods to cope with the high power loads on the divertor region of nuclear fusion reactors. Although several results have been reported using lithium less experiments were done using gallium or tin. With the purpose of comprehending the impact of the utilisation of tin on a tokamak's plasma performance it was deemed relevant to perform a series of experiments with particular emphasis on plasma contamination. In this work several diagnostics, such as Hα, bolometry, visible spectroscopy and electrostatic probes are used to characterise the interaction of plasmas with tin samples and impact this material had on the tokamak discharge performance. Liquid tin samples were exposed in the ISTTOK's edge and subject to deuterium plasmas. The sample's surface temperature was monitored by pyrometry from which plasma induced heat load was inferred. Heat loads in excess of 300 kWm−2 was regularly observed which are in agreement with Langmuir probe analysis. Hα, bolometry and plasma resistivity were used as proxies for plasma performance and these were found to remain unchanged throughout the sample exposure. The radial impurity content across the plasma column of ISTTOK is characterised by spectroscopic measurements of the Sn-II line 579.88 nm. The line intensity was found to exponentially decrease towards the plasma center with a decay length of ≈2.3 mm. These results suggest that, under specific experimental conditions, liquid tin had a negligible impact in the plasma performance of ISTTOK discharges.